Fractures of limbs specific to children: the experience of a Senegalese tertiary hospital - Florent Tshibwid A Zeng; Mbaye Fall; Papa Alassane Mbaye; Doudou Gueye; Audrey Kongo Bisseyou; Ndeye Fatou Seck; Souleymane Camara; Ibrahima Bocar Wellé; Youssouph Diedhiou; Ndeye Aby Ndoye; Aloïse Sagna; Oumar Ndour; et al. (SpringerOpen, 2022)
Abstract Introduction Fractures specific to the pediatric age group represent a particular injury due to their pattern, diagnosis, management, and outcomes. In sub-Saharan Africa, studies on this particular injury are scarce. This study reports sociodemographic, diagnostic, and therapeutic aspects and outcomes of these fractures. Methods We conducted a descriptive cross sectional study at the pediatric surgery department of Aristide Le Dantec University Teaching Hospital in Dakar, Senegal, from January 2012 to December 2015. Results A fracture specific to children was diagnosed in 180, of whom 47.7% were school-aged, with 59.4% of males. The mean time from injury to the attendance of our department was 48.2 h. Domestic accidents occurred in 51.1%. A total of 243 fractures occurred, mainly on the upper limbs (75.3%), as the most affected bones were the radius (47.3%), ulna (22.6%), and tibia (13.6%). Greenstick fractures represented 46.9%, buckle fractures, 42.8%, plastic deformations 9%, and subperiosteal fractures 0.7%. In all patients, management was orthopedic, with associated analgesic treatment. No sequel nor other complication was registered. Conclusion Fractures proper to the child are a particular entity in children's trauma, frequently happening in boys, with greenstick and buckle fractures being the most common. Their treatment is exclusively orthopedic, with excellent outcomes.